Development of Puzzle Learning Media in Islamic Religious Education Subjects Class IV Elementary School - Andini, Andini; K., Nurdin; Sudirman, Sudirman; Rahman , Syamsiah (Educational Journal of Learning Technology, 2024)
This study uses the ADDIE model to develop learning media in puzzles for Islamic Religious Education class IV subjects at SDN 304 Mamara. The goal is to assess the stage of development, validity, and practicality of the media. The research method uses a qualitative and quantitative approach with data collection techniques through observation, interviews, questionnaires, and documentation. The study results showed that the puzzle learning media was categorized as "Very Valid," with an average score of 83% from media, material, and language experts. The practicality test showed that this medium was very practical, scoring 97% from students and 82% from teachers. In conclusion, this puzzle learning media is effective and can be implemented in the learning process to increase student engagement.